2014
DOI: 10.1109/tnb.2014.2337659
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Intravenously Administered <formula formulatype="inline"><tex Notation="TeX">$\gamma-{\bf Fe}_{2}{\bf O}_{3}$</tex> </formula> Particle Amount in Mice Tissues Using Vibrating Sample Magnetometer

Abstract: Dispersions of platelet γ-Fe2O3 particles 30-50nm in size were intravenously administered to mice and the amount of particles accumulated in each tissue was obtained by magnetization measurement using a vibrating sample magnetometer. Background noise was greatly reduced by measuring dried tissues under a magnetic field of 500 Oe so that the effect of diamagnetism was slight. Remarkable particle accumulation was observed in the liver and spleen. Considerable particle accumulation was observed in the lung when a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Moreover, the time resolution of the signal is low, without the ability to be resolved in space. Another important issue that the vibration sample magnetometer has to face is the signal-to-noise ratio, which should be even more improved for this device to achieve accurate measurements [65]. In addition, according to [66], the VSM method demands a significant amount of time, and for this reason, it is not very efficient for clinical applications.…”
Section: Vibrating Sample Magnetometersmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the time resolution of the signal is low, without the ability to be resolved in space. Another important issue that the vibration sample magnetometer has to face is the signal-to-noise ratio, which should be even more improved for this device to achieve accurate measurements [65]. In addition, according to [66], the VSM method demands a significant amount of time, and for this reason, it is not very efficient for clinical applications.…”
Section: Vibrating Sample Magnetometersmentioning
confidence: 99%
“…The most important studies that use vibration sample magnetometers for nanoparticle materials characterization purposes are summarized below. Analytically, in [65], γ-Fe 2 O 3 particles, used for medical applications are measured through a vibrating sample magnetometer. In [66], a vibrating sample magnetometer is used to provide magnetic information about formalin-fixated lymph nodes, with the further aim of this information to be used to construct a clinical magnetometer, instead of the vibrating sample magnetometer.…”
Section: Vibrating Sample Magnetometersmentioning
confidence: 99%
“…Content may change prior to final publication. We previously reported that it is possible to measure the particle amount in mice tissues by using a vibrating sample magnetometer (VSM) [18].…”
Section: Introductionmentioning
confidence: 99%